Postnatal Nutrition to Improve Brain Development in the Preterm Infant: A Systematic Review From Bench to Bedside - Hortensius, Lisa M.; van Elburg, Ruurd M.; Nijboer, Cora H.; Benders, Manon J. N. L.; de Theije, Caroline G. M. (Frontiers in Physiology, 2019)
Background Preterm infants are at high risk for Encephalopathy of Prematurity and successive adverse neurodevelopmental outcome. Adequate nutrition is crucial for healthy brain development. Maternal breast milk is first choice of postnatal enteral nutrition for preterm infants. However, breast milk contains insufficient nutrient quantities to meet the greater nutritional needs of preterm infants, meaning that supplementation is recommended. Aim To provide an overview of current literature on potential nutritional interventions for improvement of neurodevelopmental outcome in preterm infants, by taking a bench to bedside approach from preclinical models of neonatal brain injury to randomized controlled clinical trials (RCTs) in preterm infants. Methods Separate clinical and preclinical searches were performed in Medline and Embase for English written papers published between 08/2008 and 08/2018 that studied a single nutritional component. Papers were included if one of the following components was studied: lipids, carbohydrates, proteins, vitamins, minerals, probiotics, prebiotics, oligosaccharides, fatty acids, or amino acids, with brain injury, brain development or neurodevelopmental outcome as outcome measure in preterm infants (gestational age <32 weeks and/or birth weight <1500 grams) or in animal models of neonatal brain injury. Results In total, 2671 preclinical studies and 852 RCTs were screened, of which 24 preclinical and 22 RCTs were included in this review. In these trials supplementation with amino acids and protein, lipids, probiotics (only clinical), prebiotics (only clinical), vitamins and minerals was studied. All included preclinical studies show positive effect of supplementation on brain injury and/or neurodevelopment. Although some nutrients, such as glutamine, show promising short term outcome in clinical studies, no evident long term effect of any supplemented nutrient was found. Main limitations were inclusion of studies no older than 10 years at time of search and studies that focused on single nutritional components only. Conclusion Even though many preclinical trials demonstrate promising effects of different nutritional interventions on reducing brain injury and/or improving neurodevelopmental outcome, these positive effects have so far not evidently been demonstrated in RCTs. More clinically relevant animal models and long term follow up after clinical trials are needed to move novel nutritional therapies from bench to bedside of preterm infants.